Optimising the ratio of long‐ to short‐chain triglycerides of the lipid phase to enhance physical stability and bioaccessibility of lycopene‐loaded beverage emulsions. (29th November 2018) - Raikos, Vassilios; Hayward, Nick; Hayes, Helen; Meroni, Erika; Ranawana, Viren
Summary: Oil‐in‐water beverage emulsions (pH3.2) with different long‐ to short‐chain triglyceride (LCT to SCT) ratios were used to encapsulate lycopene. Beverages containing 3% w/w oil from carrier lipids were prepared as follows (w/w): 100:0, 75:25, 50:50, 25:75, and 0:100 (corn oil:tributyrin). The beverages prepared using a low LCT to SCT ratio (0:100) were physically unstable mainly due to Ostwald ripening phenomena, as indicated by confocal laser microscopy. The oil droplet size was significantly reduced for emulsions formulated with corn oil (2.6 μm) compared with tributyrin (5.4 μm). Lycopene was not bioaccessible in beverages formulated with tributyrin only and bioaccessibility increased significantly with increasing the LCT to SCT ratio. Data indicated that bioaccessibility for lycopene is 2.7% for emulsions with high LCT ratios (>75). Results indicate that the carrier lipid phase of emulsion‐based systems is critical for the formulation of functional drinks for the delivery of lipophilic bioactive compounds. Abstract : The LCT: SCT ratio of the carrier oil determines physical stability and bioaccessibility of lycopene in beverage emulsions.